Locked nucleic acid-modified antisense oligonucleotides attenuate scar hyperplasia through targeted inhibition of CTGF - Li, Jinhe; Wu, Xi; Yang, Ying; Mao, Ruiqi; Li, Zherui; Zhang, Xiujun; Wei, Wenguo; Wang, Wendi; Li, Hailong; Zhou, Honggang; Yang, Cheng (Frontiers in Pharmacology, 2025)
Connective tissue growth factor (CTGF) is notably upregulated in scar tissue, making it a promising target for therapeutic intervention. Here, we have designed and screened an antisense oligonucleotide (ASO) that binds specifically to the exon five sequence of CTGF, with particular emphasis on the use of 2′-O-methoxyethyl (MOE) and locked nucleic acid (LNA) modifications to enhance stability and specificity. In vitro experiments demonstrated that both MOE-ASO#1 and LNA-ASO#1 significantly inhibited fibroblast proliferation and extracellular matrix protein expression. In vivo studies using mouse and rabbit scar models, as well as a nude mouse keloid xenograft model, revealed that these ASOs effectively reduced scar formation and keloid growth while also suppressing IL-6 expression. LNA-ASO#1 showed superior pharmacodynamics compared to MOE-ASO#1. Mechanistic investigations indicated that the ASOs exert their antifibrotic effects by inhibiting the TGF-β1 pathway, myofibroblast activation, and extracellular matrix production. These findings suggest that LNA-ASO#1 is a promising therapeutic strategy for the treatment of scars.